Literasi Digital Sebagai Jalan Penguatan Pendidikan Karakter Di Era Society 5.0 - Sugiarto; Ahmad Farid (Cetta: Jurnal Ilmu Pendidikan, 2023)
Character education is an important component in the framework of developing moral and ethical values in students. In the era of Society 5.0, where digital technology has become an important part of everyday life, digital literacy is an important factor in strengthening character education. Digital literacy refers to an individual's ability to use, evaluate, and actively participate in the digital environment. This study aims to explain the role of digital literacy in strengthening character education in the era of Society 5.0. The research method used is a literature study by collecting data from various relevant sources. This study analyzes the relationship between digital literacy and strengthening character education by considering aspects such as technological knowledge, digital skills, responsible online media behavior, and ethical awareness in the digital world.  The results show that digital literacy can be an effective way to strengthen character cultivation in the era of society 5.0. Through digital literacy, learners can develop values such as honesty, responsibility, empathy, cooperation, and problem solving. Digital literacy can also help learners understand social, economic, and cultural impacts and promote responsible attitudes in their use. In conclusion, digital literacy has an important role in strengthening character education in the era of Society 5.0. By paying attention to aspects of technological knowledge, digital skills, responsible online behavior, and ethical awareness, digital literacy can help learners develop strong moral and ethical values in the use of digital technology. Collaborative efforts between various parties are needed to overcome challenges and ensure effective integration of digital literacy in character education in the era of Society 5.0.